Development and Characterization of Sustained Release Solid Dispersions of Chlorzoxazone - Nanjappa, Shivakumar Hagalavadi; Samreen, Ayesha; Kumar, Avichal; Shinde, Rushikesh (Indian Journal of Pharmaceutical Education and Research)
Objectives: The research aimed to develop Sustained Release Solid Dispersions (SRSDs) of Chlorzoxazone (COZ) to improve therapeutic efficacy and patient compliance. Materials and Methods: SRSDs were developed by the bottom-up solvent evaporation technique with various polymers, comprising Eudragit RL100, ethyl cellulose, Eudragit RS100, and cellulose acetate. Results: All eight SRSDs batches exhibited good flow properties with the Carr’s index, angle of repose, and Hausner’s ratio ranging from 11.56±0.01 to 14.89±0.02, 22.03±0.02º to 25.24±0.03º, and 1.11±0.05 to 1.24±0.03, respectively, indicating suitability for further processing. Drug loading and percentage yield were found to range between 72.28±2.36 to 88.25±2.78% and from 65.23±2.23 to 90.41±2.97% respectively. SEM and optical microscopy revealed the reduction in size of the SRSDs, while Fourier transform infrared spectroscopy proved the drug integrity in the formulations. X-ray diffraction and Differential Scanning Calorimetry confirmed a drop-in drug crystallinity in the SRSDs. The in vitro drug release studies of SRSDs were found to range from 62.32±5.4% to 94.93±9.81% in 8 hr. Batch F5 emerged as the best formulation, displaying the most desirable drug release profile with minimal burst effect (29.97±2.75% in 1 hr) and 78.11±6.18% at 8 hr. The drug release from F5 appeared to follow first-order kinetics governed by Higuchi diffusion and Fickian transport mechanisms. Conclusion: The studies proved that the bottom-up solvent evaporation method was employed to successfully produce SRSDs of COZ, which prove to be an ideal platform that can ensure a prolonged, yet complete release of the drug.
Keywords: Chlorzoxazone; Bioavailability; Sustained release solid dispersions; Solvent evaporation